The Problem of Ethnic Minorities in Stasys Šalkauskis' Conception Nationality - Ivanovas, Bernaras (Sociologija. Mintis ir veiksmas, 2001)
This article is dedicated to the problem of nationality in the works of Lithuanian philosopher Stasys Šalkauskis. Philosopher was strongly influenced by political changes of that period of time. He was living and working during the time of democracy (till coupe d’eta in 1926), so his concept was more democratic then the concepts of other philosophers who were writhing in the four decade. But generally we can say, that the attitude of there Lithuanian philosophers to the problems of nationality, that consists such parts as the patriotism, national minorities, language, historical conciseness, nationalism, is very close to premordialistic conception, that in national identity emphasises just natural features that man got in the moment of birth. On another hand, Šalkauskis unlike premordialists but more like transformists try to define the evolution of the Lithuanian ethnos. The final part of this evolution is transformation from ethno structure to nation. So, we can detect here three main components that reflect three main tendencies in the theory of nationalism (primordialism, evolutionism and constructivism) in the national theory of Šalkauskis: 1. Emphasis of national nature as a ‘given’; 2. Existence of national evolution and transformation; 3. Formation of modern ethnos to nation, as the most important condition of execution of national vocation, that would lead to a new level of identity. At the end we can say that the Šalkauskis’ concept of nationality sintesize this entire three components ant that guarantee the originalities of the Lithuanian philosophers works.
Keywords: Stasys Šalkauskis; nationality; ethnic minority; Lithuanian philosophy; sociological theory of nationalism